2018
DOI: 10.1016/j.brs.2018.07.048
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high-frequency transcranial random noise stimulation (hf-tRNS) on global motion processing: An equivalent noise approach

Abstract: hf-tRNS interacts with the output neurons tuned to directions near to the directional signal, incrementing the signal-to-noise ratio and the pooling of local motion cues and thus increasing the sensitivity for global moving stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 64 publications
0
37
1
Order By: Relevance
“…Corticospinal excitability was assessed by measuring the amplitude of MEPs of the first dorsal interosseous (FDI) by TMS over M1 using a Magstim Rapid 2 stimulator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticospinal excitability was assessed by measuring the amplitude of MEPs of the first dorsal interosseous (FDI) by TMS over M1 using a Magstim Rapid 2 stimulator.…”
Section: Methodsmentioning
confidence: 99%
“…The modulatory effects of tRNS – mainly involving the high-frequency band – have been probed with different motor, sensory and cognitive tasks. Studies on sensory or perceptual processing showed, for example, that hf-tRNS can improve visual detection or discrimination 24 and can enhance the perception of facial identity 5 and facial expression of emotions 6,7 . Visual motion adaptation, on the other hand, has shown to be either attenuated or enhanced depending on the frequency band used 8 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the detection of low-contrast visual stimuli was significantly enhanced when the stimuli were superimposed with visual noise (Simonotto et al 1997). Recently, a similar enhancement of visual perception has been reported when noise was directly added to visual cortex via tRNS, which improved the detection of low contrast visual stimuli (van der Groen and Wenderoth 2016), visual decision making (Ghin et al 2018;Pavan et al 2019;van der Groen et al 2019), binocular rivalry (van der Groen et al 2018), and visual training in healthy participants (Fertonani et al 2011;Pirulli et al 2013) and patients (Moret et al 2018;Herpich et al 2019).…”
Section: Introductionmentioning
confidence: 64%
“…similar to the no noise condition) is currently unknown. Possible mechanisms might be that high intensity tRNS perturbs the sampling or processing of sensory information (Ghin et al 2018;Pavan et al 2019), the "sharpness" of neural representations of the external stimulus or the process of evidence accumulation (van der Groen et al 2018), which are part of perceptual decision making. Accordingly, high tRNS intensities might cause "false alarms".…”
Section: Acute Trns-induced Noise Benefits Are Partly Consistent Withmentioning
confidence: 99%
“…There has been a burgeoning growth in recent years of studies investigating the application of tRNS to enhance sensory processing (Ghin et al, 2018;K. S. Rufener et al, 2018;Contemori et al, 2019), motor performance (Abe et al, 2019;Jooss et al, 2019), and cognition (Snowball et al, 2013;Popescu et al, 2016;Mammarella et al, 2017;Shalev et al, 2018;Tyler et al, 2018) in healthy participants with largely promising results.…”
Section: Introductionmentioning
confidence: 99%